On exhaustive vector measures (1994)
Certain conditions related with the De Wilde and Valdivia closed graph theorems enable us to guarantee the exhaustivity of certain bounded vector measures. To obtain some of the e conditions we show incidentally that  the bounded countably valued scalar function space with the supremum norm is ultrabornological.